Failure analysis of hydraulic rotary drill rods in a limestone mine - Anirut Chaijaruwanich (2018)
© 2016 Int. J. Mech. Eng. Rob. Res. Failure analysis of two hydraulic rotary drills used for rock drilling was carried out. Chemical analysis, metallurgical examination, surface fractography and hardness measurement were used for the analysis. The failed drill rods composition matched with low alloy 31NiCrMo13-4 grade steel. The hardness measurement results suggested that the drilled rods were surface hardened. Surface fractography examination revealed that crack initiation of the fractured drill rods started at the outer surface, especially at the joint between the drill rod and drill bit. The mode of failure was found to be fatigue. The stress concentration locating at groove of threads at the joint was likely to cause the crack initiation. Propagation of fracture was observed with the evidence of beach mark, resulting from continuous nominal low stress.